Penyelesaian Sengketa Bidang Ekonomi Melalui Arbitrase dan Alternatif Penyelesaian Sengketa (APS) - Safira, Martha Eri (Justicia Islamica, 2009)
This study aims to analyze the application of arbitration and alternative dispute resolution (ADR) in the economic field as an effective and efficient method of dispute resolution. Using a qualitative method with a case study approach, this study examines the practice of arbitration and ADR in resolving economic disputes, both at the national and international levels. The results show that arbitration and ADR can be a faster and more flexible alternative compared to the formal judicial process, but require clear regulations and transparency in their implementation. Another advantage is its ability to reduce the burden on the courts and maintain good relations between the parties in dispute. This study suggests the need for stronger regulations and a broader understanding of arbitration and ADR among economic actors.